Adiponectin Levels Are Associated with White Matter Lesions (WMLs) and Cognitive Impairment. (18th January 2022) - Quan, Hui; Yu, Tongya; Lin, Yingying; Pan, Jie; Mao, Bingjie; Wang, Xuan; Xie, Junchao; Liu, Xueyuan; Zhao, Yanxin
Abstract : Background and Objective . White matter lesions (WMLs) are imaging changes characterized by hyperintensities on T2-weighted or FLAIR images, which are closely related to the decline of cognitive function. However, the etiology and pathogenesis of WMLs remain undetermined. The aim of this study was to analyze the relationship between adiponectin levels and cognitive decline in persons with or without white matter lesions. Method . In the present study, 126 patients, 90 cases in the WML group and 36 cases in the control group, were analyzed to explore the relationship between adiponectin and WMLs. All patients underwent an MRI scan to assess whether white matter lesions happened. And the serum levels of adiponectin were detected by ELISA. Results . In this study, according to Fazekas criteria, WMLs were divided into different severity groups. With the increase of WML score, the level of adiponectin decreased, and linear correlation analysis shows that adiponectin is negatively correlated with the severity of white matter lesions (p < 0.001 ). And adiponectin level was significantly positively correlated with MoCA score (p < 0.05 ). Moreover, adiponectin in the WMLs combined with the cognitive impairment group was significantly reduced (p < 0.01 ). Conclusion . The level of adiponectin is independently associated with WMLs and cognitive function, which suggests that adiponectin may be a protective factor for WMLs and cognitive function.